Cybercafe system using client-server application - Farhana, Abdul Samad (2011)
Cybercafé System is software for operating Internet Café, Cybercafé,Game Centre,Gaming Café and PC rental Café shop. It has been designed for make ease to the management, accounting,billing even it can be used for intranet PC controlling.There are six chapters altogether inside the report.The first chapter is the introduction.This chapter will discuss about the preface of the system and it briefly explains about the objectives of the system,problem statement that occurred to build the system and the system's scopes.Chapter two and three are the literature review and research and methodology respectively.Chapter two and three will be elaborating on the sources from the research,deciding and discussing the method that will be used in developing the system and the best tools that will be used to build the system.Next,chapter four will be the implementation.This chapter will be discussing on the documentation of the processes during the development of the system,including any modification that been planned and made.Chapter five will be the results and discussion.This chapter will explain about the results that have been collected from the analysis and testing of the system along with the constraints and suggestions to enhance the system's performance in the future.The last chapter will be the conclusion.This chapter will give the summary of the system, data,methodology,implementation and the suggestions of the system.